Breeding Biology of King Eiders Nesting on Karrak Lake, Northwest Territories - Kellett, Dana K.; Alisauskas, Ray T. (ARCTIC, 1997)
We studied various aspects of the breeding biology of king eiders (Somateria spectabilis) nesting at Karrak Lake, south of Queen Maud Gulf in the central Canadian Arctic. We found 41 nests distributed among 10 islands in Karrak Lake; to our knowledge, this represents the largest number of king eider nests studied at one site. We suspect that island nesting by king eiders is more common than has been previously reported. King eiders favoured mid-sized islands (0.002-0.081 km²) over very small (less than 0.002 km²) or very large (greater than 0.081 km²) islands. Mean clutch size was 5.4 ±1.7 (SD) eggs. Apparent nest success was 69.4% with a composite Mayfield estimate of nest success over egg laying and incubation of 48.7% (95% CI: 47.4-50.0%). Nest success was uncorrelated with date of nest initiation or island size, but eiders nesting on islands farther from the mainland had greater success than those nesting on islands closer to the mainland. Additionally, nest success was greater on islands with more nesting eiders and on islands with nesting arctic terns (Sterna paradisaea). On a étudié divers aspects de la biologie reproductive de l'eider à tête grise (Somateria spectabilis) nichant au lac Karrak, qui se trouve au sud du golfe de la Reine-Maud, au centre de l'Arctique canadien. On y a trouvé 41 nids répartis sur 10 îles situées dans le lac Karrak; à notre connaissance, cela représente le plus grand nombre de nids d'eiders à tête grise faisant l'objet d'une étude sur un seul site. On soupçonne que l'eider à tête grise niche plus couramment dans des îles qu'on ne l'avait rapporté précédemment. Les individus préféraient les îles de taille moyenne (0,002 à 0,081 km²) aux îles très petites (moins de 0,002 km²) ou très grandes (plus de 0,081 km²). La taille moyenne des couvées était de 5,4 oeufs, avec un écart-type de 1,7. Le taux d'éclosion apparente était de 69,4 p.cent, avec une estimation composée de Mayfield de 48,7 p.cent (intervalle de confiance au seuil de 95 p.cent: 47,4 à 50,0 p.cent) pour le succès de ...